Power and Politeness: A Pragmatic Analysis of Managerial Hierarchies in School Settings - Lastri Wahyuni Manurung; Benya Lertsuwan; Eka Putri Saptari Wulan; Carolina Carolina (Universitas Pendidikan Mandalika, 2026)
This study investigates how power relations influence the use of politeness strategies in direct communication within a hierarchical school environment. Grounded in Brown and Levinson’s (1987) politeness theory and the pragmatic perspective of speech acts, the research aims to identify the types and sub-strategies of politeness used by speakers, examine how hierarchical status affects linguistic choices, and interpret the implied meanings behind politeness in institutional interactions. Using a qualitative descriptive design, data were collected through natural conversations and contextual interviews involving participants at different managerial levels: headmaster, vice principals, teachers, students, and cleaning staff. The findings reveal a strong tendency toward negative politeness (82.70%), expressed through apology, hedging, deference, and indirectness, reflecting a heightened awareness of institutional hierarchy. Positive politeness (9.20%) appears in horizontal interactions emphasizing solidarity, while off-record politeness (8.10%) is used primarily by lower-status participants to minimize social risk. These patterns demonstrate that linguistic politeness functions as a pragmatic tool for negotiating power and maintaining harmony in the school context. The study contributes to a deeper understanding of language use in hierarchical educational environments and highlights the importance of strengthening pragmatic awareness among school personnel. Practically, the results imply the need for communication training programs that help teachers and school leaders develop respectful, effective, and context-sensitive communication practices.